Chlamydia trachomatis Infection Is Related to Poor Semen Quality in Young Prostatitis Patients - Mazzoli, Sandra; Cai, Tommaso; Addonisio, Patrizia; Bechi, Adriano; Mondaini, Nicola; Bartoletti, Riccardo (European urology, 2010)
The impact of chronic prostatitis resulting from Chlamydia trachomatis infection on male fertility is controversial. To investigate the correlation between C. trachomatis infection and semen quality in young male patients affected by chronic prostatitis resulting from C. trachomatis infection and to evaluate the correlation between anti–C. trachomatis immunoglobulin (Ig) A against heat shock protein 60 (HSP60), heat shock protein 70 (HSP70), and semen parameters. All patients with clinical and instrumental diagnosis of chronic prostatitis underwent microbiological cultures for common bacteria, DNA extraction, mucosal and serum antibody evaluation for C. trachomatis, and semen parameter analysis. Western blot analysis of mucosal anti–C. trachomatis IgA was performed. Subjects were split into two groups: Group A consisted of patients with chronic prostatitis resulting from common bacteria (uropathogens), and group B consisted of patients with chronic prostatitis resulting from C. trachomatis infection. The relationship between C. trachomatis infection and semen parameters as well as the correlation among IgA levels, IgA characterisation, and semen analysis were determined. We enrolled 1161 patients (mean age: 36.5 yr). Of these, 707 patients were placed in group A, and 454 were placed in group B. Significant statistical differences were reported between groups in terms of sperm concentration (p<0.001), percentage of motile sperm (p<0.001), and normal morphologic forms (p<0.001). Strong correlations between mucosal anti–C. trachomatis IgA and sperm concentration (p<0.001) and normal morphologic forms (p<0.001) were reported. Correlations among positivity to HSP60, HSP70, and sperm concentration (p<0.003) and normal morphologic forms (p<0.001) were also reported. This study demonstrated the role of chronic prostatitis resulting from C. trachomatis in male fertility decrease, highlighting probable immunomediated damage to germinal cells because of C. trachomatis infections. This study demonstrated the role of Chlamydia trachomatis in decreasing male fertility in a large cohort of young males affected by chronic bacterial prostatitis, highlighting the probable immunomediated damage to germinal cells resulting from C. trachomatis infections.